NOx emissions in India derived from OMI satellite observations. (April 2022) - Ding, Jieying; van der A, Ronald; Mijling, Bas; de Laat, Jos; Eskes, Henk; Boersma, K. Folkert
Abstract: The fast industrialization and urbanization in India lead to serious air quality problems. Using the long record of the satellite observations of NO2 from the Ozone Monitoring Instrument, we have derived monthly NOx emissions over India from 2007 to 2018 by applying an inversion algorithm to the QA4ECV NO2 retrieval product. Our results show that NOx emissions steadily increased by more than 50% from 2007 until 2016. From 2017 onwards, NOx emissions have become stable or are slowly decreasing. Furthermore, our results also reveal a strong seasonal cycle in the emission with the peak in summer, partially caused by biogenic/soil NOx emissions that is one of the main NOx sources in India. The validation of our derived NOx emissions with HTAP, Global power plants database and in-situ observations show that the spatial distribution and quantity of NOx emissions are well captured. The long-term record of NOx emissions captures the trend over India well and illustrates the impact of air quality measures on air pollution in India. Highlights: We have estimated long-term NOx emissions over the Indian area based only on OMI satellite observations. The trend from 2007 to 2018 and seasonal of NOx emissions are analysed. We have distinguished the soil and anthropogenic emissions in the region. The derived emissions have been verified and validated with the HTAP bottom-up emission inventory and in-situ observations.